Peranan Harga dan Digital Marketing Pada Penjulan Barang di Butik D’Scarpa Shop Medan Sumatera Utara - Deanti Indira; Ihsan Effendi; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to determine the role of price and digital marketing in the D'Scarpa Shop Medan boutique. This type of research is qualitative research, namely research on descriptive research and tends to use analysis. The results of this study, it can be concluded that the price and digital marketing used by D'Scarpa Shop Medan boutique is very important and successful in increasing sales. Prices are set according to the quality of goods, capital goods and the intended market so that they can be affordable by the buyer. Digital marketing used is Instagram social media where sales of the D'Scarpa Shop Medan boutique are 70% via Instagram and sales have increased from 2013 to 2019.